2017
DOI: 10.1038/s41467-017-00746-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic microparticles conjugated with VEGF165 improve the survival of endothelial progenitor cells via microRNA-17 inhibition

Abstract: Several cell-based therapies are under pre-clinical and clinical evaluation for the treatment of ischemic diseases. Poor survival and vascular engraftment rates of transplanted cells force them to work mainly via time-limited paracrine actions. Although several approaches, including the use of soluble vascular endothelial growth factor (sVEGF)—VEGF165, have been developed in the last 10 years to enhance cell survival, they showed limited efficacy. Here, we report a pro-survival approach based on VEGF-immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Furthermore, to clarify the effect of LSS on CTC survival in more detail, we elucidated the mechanobiological mechanism of ATOH8-meditated response to LSS in CRC m-CTCs. In the past, scholars discovered that LSS promoted VEGF secretion and inhibited cell apoptosis in endothelial cells [52][53][54]. Moreover, increasing evidence has indicated that LSS mediates tumour Mechanically, in CRC m-CTCs responding to LSS stimulation, VEGF activates the downstream AKT pathway by acting on the VEGFR2 receptor, thereby facilitating ATOH8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to clarify the effect of LSS on CTC survival in more detail, we elucidated the mechanobiological mechanism of ATOH8-meditated response to LSS in CRC m-CTCs. In the past, scholars discovered that LSS promoted VEGF secretion and inhibited cell apoptosis in endothelial cells [52][53][54]. Moreover, increasing evidence has indicated that LSS mediates tumour Mechanically, in CRC m-CTCs responding to LSS stimulation, VEGF activates the downstream AKT pathway by acting on the VEGFR2 receptor, thereby facilitating ATOH8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro nifedipine treatment increases VEGF secretion from human coronary artery smooth muscle cells by PKC activation via the bradykinin B2 receptor . VEGF has been reported to enhance EPC differentiation for angiogenesis and vascular repair . The effects of methyldopa on cell proliferation and migration have seldom been reported, especially on EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, when envisioning in vitro generated 3D microtissues implantation, the establishment of highly dense constructs is generally deleterious due to decreased oxygen/nutrients diffusion. Recent efforts have been made toward surpassing these issues through the development of VEGF 165 ‐functionalized microcarriers, or of oxygen releasing microparticles that increased the viability of 3D cellular masses cultured in microparticulated platforms . The latter is a particularly elegant approach that has proven valuable for providing a timely supply of oxygen to microparticle adhered human‐periosteal‐derived cells which preserved their osteogenic differentiation even under hypoxia …”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%